2018
DOI: 10.1039/c8sm01193a
|View full text |Cite
|
Sign up to set email alerts
|

Bending nematic liquid crystal membranes with phospholipids

Abstract: The interactions of phospholipids with liquid crystals have formed the basis for attractive biosensor technologies, but many questions remain concerning the basic physics and chemistry of these interactions. Phospholipids such as 1,2-dilauroyl-sn-glycero-3-phosphocholine (DLPC), at sufficiently high (∼1 μM) concentrations and/or sufficiently long times, turn the liquid crystal director perpendicular to the LC/water interface. If the other side of the LC film is in contact with a surface that prefers perpendicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Revisiting the POM photograph with uncrossed polarizers in Figure , we note that the central parts of both the ring-forming and the dark droplets (the latter marked with a white arrow) have a different color than in their periphery, which can be associated with the bent profile revealed by AFM observations. It can be hypothesized that the bending occurs as a result of the packing of IL headgroups coupled with the smectic nature of 8CB, , facilitating altogether the ring formation of TFCDs.…”
Section: Resultsmentioning
confidence: 99%
“…Revisiting the POM photograph with uncrossed polarizers in Figure , we note that the central parts of both the ring-forming and the dark droplets (the latter marked with a white arrow) have a different color than in their periphery, which can be associated with the bent profile revealed by AFM observations. It can be hypothesized that the bending occurs as a result of the packing of IL headgroups coupled with the smectic nature of 8CB, , facilitating altogether the ring formation of TFCDs.…”
Section: Resultsmentioning
confidence: 99%
“…The CLC droplets underwent tistage reconfigurations, which initiated from the interface and propagated to the (Figure 1A). Since DLPC amphiphiles form vesicles above 100 nM [39], at the conc tions used in this study, they were assumed to interact with the CLC interface in th icle form, at which the hydrophobic tails and acyl chains interdigitated into the CLC ecules. The vesicles reoriented at the interface, and upon penetration of their acyl c between the CLC molecules, their zwitterionic head groups packed at the interface vious studies have reported the transition from bipolar to radial configuration in ne microdroplets in the presence of phospholipid amphiphiles.…”
Section: Dynamic Molecular Reconfiguration Of High-chirality Droplets...mentioning
confidence: 99%
“…[92][93][94] Other amphipathic molecule such as aliphatic acids, phospholipids, and lipopolysaccharides can also play the similar role. [95][96][97] In addition, for saline solutions, the LC alignment at the interface can be decided by the solutes. [98] For example, solutes such as iodide, perchlorate, and thiocyanate have large ionic radius and weak hydration and therefore favor the perpendicular alignment.…”
Section: Alignmentsmentioning
confidence: 99%